Anisotropic Ferro- and Dielectric Properties of Textured Bi4Ti3O12 Ceramics Prepared by the Solid-State Reaction Based on Multiple Calcination - Xiangyu Mao; Wei Wang; Hui Sun; Xiaobing Chen (Advances in Materials Science and Engineering)
The grain-oriented Bi4Ti3O12 (BIT) samples were prepared by the solid-state reaction method with a multicalcination process. The grain-oriented BIT samples exhibit anisotropic structural, ferroelectric, piezoelectric, and dielectric properties. The remanent polarization (2Pr) and the piezoelectric constant (d33) of a/b- and c-direction BIT ceramics are 49.5 μC cm−2, 22.2 pC N−1 and 6.7 μC cm−2 6.9 pC N−1, respectively. The dielectric anomalies of samples are observed around 157 K and 232 K. The dielectric anomalies at around 157 K are related to oxygen vacancies. The activation energy of the dielectric relaxation of this anomaly is estimated to be 1.36 eV. Another dielectric anomaly at around 232 K is related to polarizable domains and the viscous motion of domain walls.